PENGARUH BUDAYA ORGANISASI, MOTIVASI KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI KANTOR KECAMATAN PANGKALBALAM KOTA PANGKALPINANG - Edi Susandi; Reniati; Hamsani (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the influence of organizational culture, work motivation, and physical work environment on the performance of employees at the Pangkalbalam District Office, Pangkalpinang City. The research is motivated by the phenomenon that the performance of the Pangkalbalam District Office has not yet reached an optimal level, as reflected in the Performance Accountability Report (LAKIN), where several activities have not been fully achieved. The suboptimal performance of employees is indicated to be influenced by the organizational culture, work motivation, and the physical work environment at the office. This study is a descriptive quantitative research involving 32 respondents. The sampling technique used is saturated sampling. The independent variables in this research are organizational culture, work motivation, and physical work environment, while the dependent variable is employee performance. The analytical method applied is multiple linear regression analysis. The results show that organizational culture (t = 2.788 > t-table = 1.701), work motivation (t = 2.727 > t-table = 1.701), and physical work environment (t = 2.945 > t-table = 1.701) each have a positive and significant partial effect on employee performance at the Pangkalbalam District Office. The simultaneous test results indicate that organizational culture, work motivation, and physical work environment together have a positive and significant effect on employee performance, with an F-count of 13.596 > F-table of 2.95.